Redesign of rails for overhead systems : A development work to make the system more efficient - Pettersson, Sandra; Strålberg, Emma (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2017)
In hospitals and healthcare facilities lifts are often used to help caregivers transfer caretakers from one place to another, or to help caretakers during their rehabilitation training. In facilities where different people are being helped with everyday tasks or treated for injuries and sicknesses, it is common to install an overhead system. An overhead system consists of one or several slings, motors and rails that are mounted primarily in the ceiling but can also be mounted against walls or on upright supports. This project is a master thesis in Industrial Design Engineering written during the spring of 2017 at Luleå University of Technology and Liko Hill-Rom in Alvik, Luleå. The main focus of this project will be on developing the rails in the overhead system to make the system more efficient and reduce the overall cost. The goal was to develop the rails of the existing overhead system in order to deliver a concept that makes the whole system more efficient with fewer variations. The project has been conducted using a human centered design approach, meaning that the stakeholders have been involved in the process to ensure that the design is beneficial. The main stakeholder for this project Liko Hill-Rom, have not only been a part of the information gathering or the evaluation of the concepts but also in the creative process. Other theories such as ergonomics, manufacturing methods and gestalt perception have been used throughout the project to ensure a result with scientific support. The overall objective was to seek areas of improvements and to develop the rails to meet up with given specifications such as technical requirements and design specifications. Throughout the process different design methods have been applied to help the group create a concept that the stakeholders will benefit from. The result is a new rail concept that eliminates the high numbers of rails that the client offers today. This is done without reducing the capability to carry high loads and is a system that is adapted to create a ...